Oferta académica de la Universidad Técnica Estatal de Quevedo y su relación con la demanda de profesionalización de los bachilleres del cantón: año 2015. - Baez Oñate , Marcos Vinicio (2025)
This research "ACADEMIC OFFER OF TECHNICAL STATE UNIVERSITY QUEVEDO AND ITS RELATIONSHIP WITH THE DEMAND FOR PROFESSIONAL DEVELOPMENT OF THE CANTON BACHILLERES: 2015" emerges as a pressing need for guidance with responsibility, the top-level careers that offer the graduates of the city, to meet the high student demand at the university level.